Identification Research of the Concept of Entrepreneurship: The Theoretical Aspect - Giriuniene, Gintare; Giriunas, Lukas; Cernius, Gintaras (International Journal of Economics and Financial Issues, 2016)
It should be noted that entrepreneurship and its promotion is increasingly becoming a subject for research. Since in most cases entrepreneurship is analysed in interdisciplinary sciences as well as in different aspects, there are often found distinct discrepancies of the concept outline. It should be emphasized that, in scientific research, it is very important that the same concept is referred to the same phenomenon; therefore, the article deals with unified presentation options of the concept of entrepreneurship. A detailed analysis of scientific literature has shown that the presentation of a single concept of entrepreneurship, which could be used in interdisciplinary sciences, would enrich the social sciences. Thus, the aim of the research is to present a single graphical annotation of the concept of entrepreneurship characterized by interdisciplinarity after having investigated entrepreneurship concept variations found in the scientific literature. To achieve this, a study of international scientific literature and the analysis of published reliable empirical research were conducted as well as the methods of induction, deduction, comparative analysis, intellectual intuition and logical investigation were used in this article. The research of the concept of entrepreneurship carried out in the theoretical aspect enabled to form and justify the interdisciplinary concept of entrepreneurship. Keywords: concept of entrepreneurship; interdisciplinarity. JEL Classifications: H00; L26